Samuel Beckett in context - Uhlmann, Anthony (Cambridge ; New York : Cambridge University Press, 2013)
"When Samuel Beckett first came to international prominence with the success of Waiting for Godot, many critics believed the play was divorced from any recognizable context. The two tramps, and the master and servant they encounter, seemed to represent no one and everyone. Today, critics challenge the assumption that Beckett aimed to break definitively with context, highlighting images, allusions, and motifs that tether Becket's writings to real people, places, and issues in his life. This wide-ranging collection of essays from 37 renowned Beckett scholars reveals how extensively Beckett entered into dialogue with important literary traditions and the realities of his time. Drawing on his major works, as well as on a range of letters and theoretical notebooks, the essays are designed to complement each other, building a broad overview that will allow students and scholars to come away with a better sense of Beckett's life, writings, and legacy"--
Includes bibliographical references and index.
Keywords: Beckett, Samuel, -- 1906-1989 -- Criticism and interpretation; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh